2016
DOI: 10.1016/j.jpowsour.2015.11.066
|View full text |Cite
|
Sign up to set email alerts
|

Combustion synthesized copper-ion substituted FeAl2O4 (Cu0.1Fe0.9Al2O4): A superior catalyst for methanol steam reforming compared to its impregnated analogue

Abstract: A series of copper ion substituted MAl2O4 (M= Mg, Mn, Fe and Zn) spinels is prepared by a single step solution combustion synthesis (SCS) and tested for methanol steam reforming (MSR). The copper ion substituted Cu0.1Fe0.9Al2O4 appears to be the most active, showing ~98% methanol conversion at 300 °C with ~5% CO selectivity at GHSV= 30000 h-1 and H2O:CH3OH= 1.1. The analogous impregnated catalyst, CuO (10 at.%)/FeAl2O4, is found to be much less active. These materials are characterized by XRD, H2-TPR, BET, HRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 47 publications
(74 reference statements)
3
15
0
Order By: Relevance
“…Although the formal valence state of Cu ions does not cross over to 2þ, as the absorption edge for CuO, an oxide of copper with a 2þ valence state is at least 5 eV higher than the pure Cu -metal. 33 However, we observe a slight shift ($0.7 eV each) towards higher energy with increasing Ticontent. This slight change in absorption energy, though not an indication of any significant oxidation of Cu ions, suggests that subtle changes in the electronic structure of CuCrO 2 take place with Ti addition.…”
Section: -4mentioning
confidence: 62%
“…Although the formal valence state of Cu ions does not cross over to 2þ, as the absorption edge for CuO, an oxide of copper with a 2þ valence state is at least 5 eV higher than the pure Cu -metal. 33 However, we observe a slight shift ($0.7 eV each) towards higher energy with increasing Ticontent. This slight change in absorption energy, though not an indication of any significant oxidation of Cu ions, suggests that subtle changes in the electronic structure of CuCrO 2 take place with Ti addition.…”
Section: -4mentioning
confidence: 62%
“…The small shoulder observed at 850 °C is related to the reduction of nickel aluminate spinel. From Figure b, the TPR curve of the Fe 1 Al 3 O x support reveals a peak, which is attributed to the reduction of the FeAl 2 O 4 spinel . The reduction peak related to nickel oxide starts at a temperature of about 430 °C and reached a maximum at around 690 °C.…”
Section: Resultsmentioning
confidence: 92%
“…Their microstructure analysis revealed that copper ionic substitution facilitates the spinel formation during combustion and leads to the SCS catalyst with significantly high crystallinity. The catalysts with the Cu 2+ ion sites proved to be more active than the dispersed CuO nanocrystallites on the FeAl 2 O 4 impregnated catalyst, although they had lower specific surface area …”
Section: Hydrogen Production Processesmentioning
confidence: 98%